Incidencia de fasciola hepática en bovinos faenados en la ciudad de Milagro provincia del Guayas - Gaibor Carpio, Mónica Gabriela (2023)
Fasciolosis is a serious animal health problem in many rural and urban areas of the world, causing significant economic losses due to decreased production and seizure of viscera in animals. In addition, accurate diagnosis of Fasciolosis has always been a challenging task for veterinarians. This research presents a study of the incidence of fasciola hepatica in cattle slaughtered in the city of Milagro, province of Guayas. The study population is the 400 cattle slaughtered between February and March 2023. The incidence rate is 0%. There were no economic losses during the research period due to deworming controls and climatic conditions on the coast of Ecuador that help prevent the reduction of trematode infestations. Therefore, livestock production in the City of Milagro in the province of Guayas is efficient, but this does not mean that Fasciola hepatica does not help. Therefore, it is important for governments to implement campaigns to prevent and control its spread with an integral and global approach.